The Revised Common Rule and Mental Illness: Enduring Gaps in Protections - Smilan, Lisa E. (American journal of law & medicine, 2020)
In 2003, a young man with severe mental illness allegedly was coerced by his psychiatrist, against the wishes of his mother, to participate in “the CAFÉ study,” a clinical trial comparing atypical antipsychotics, including Seroquel, in first-episode psychosis; the study was conducted within the University of Minnesota Department of Psychiatry and sponsored by AstraZeneca, the manufacturer of Seroquel.4 In 2004, while still enrolled in the study and taking Seroquel, the young man committed suicide by violent and gruesome means.5 The State of Minnesota commissioned a 2015 report that showed evidence of coercive enrollment, inadequate supervision of both subjects and study personnel, conflicts of interest, and numerous misrepresentations and unethical cover-ups.6 Though some bioethics and mental health policy professionals have signaled that human research protections for mentally ill people are insufficient,7 any efforts to remedy deficiencies repeatedly miss the mark. 18 Additional sources of vulnerability may include the mental illness itself and psychotropic drugs used to treat the illness, both potentially altering the patient-participant’s authentic self through their effects on thought processes and choices.19 Further, the power imbalance within the psychiatrist-researcher patient-participant relationship—sometimes referred to as “power-relational vulnerability” or deferential vulnerability20—is another source of vulnerability that may go unrecognized.21 Given the history of stigmatization and abuse against mentally ill people, both outside22 and within the research context,23 regulations and guidance should impose heightened protections for this population to ensure proper enrollment and continued participation in biomedical research. At least one of these IRB members should be a member of the population being studied, a family member of such a person, or a representative of an advocacy organization for this population.34 Official guidance based on these 1998 recommendations would have been appropriate, but federal regulators issued no guidance specifically limiting risks to which mentally ill participants might be exposed in biomedical research.35 Due to the heterogeneity of people who suffer from mental illnesses, and the variability of mental illnesses even within diagnostic categories, a detailed, one-size-fits-all rule may have been beyond realistic expectation.36 But the fact that a task is challenging does not warrant avoiding or abandoning attempts to address it. The term “mentally disabled” is the closest approximation to mental illness in the original Common Rule.41 Who was “mentally disabled” or what constituted a mental disability was never properly defined under the original rule, and whether or not it was intended to include people with mental illness is unknown.42 The Americans with Disabilities Act definition of “disability” includes a “mental impairment that substantially limits one or more major life activities of an individual,”43 yet the term “mental disability” has many mainstream connotations, including congenital brain abnormalities and cognitive deficits from brain damage or